Radioprotective effect of epimedium on neurogenesis and cognition after acute radiation exposure. (August 2019) - Wang, Si Wei; Ren, Bo Xu; Qian, Feng; Luo, Xue Zhi; Tang, Xi; Peng, Xiao Chun; Huang, Jiang Rong; Tang, Feng Ru
Highlights: Acute irradiation with 5.5 Gy induced impairment of neurogenesis. Herb epimedium (or yin yang huo) extract is radioprotective. Epimedium extract prevented radiation-induced loss of proliferation cells and newly generated neurons. Epimedium extract prevented radiation-induced depression and spatial learning and memory. Abstract: The radioprotective effect of herb epimedium (or yin yang huo) extract (5 g/kg, oral administration daily for 4 weeks) on neurogenesis and cognition after acute radiation exposure with 5.5 Gy was evaluated in Balb/c mice by behavioral tests and immunohistochemical study. The results indicated that epimedium extract could improve animal weight loss, locomotor activity and spatial learning and memory which are similar to pre-irradiation intraperitoneal injection (100 mg/kg) of amifostine phosphate, a well- known radioprotective drug. Immunohistochemical study showed that epimedium extract prevented the loss of proliferation cells, newly generated neurons, and interneurons in the hilus, in particular, the subgranular zone of the dentate gyrus. It suggests that herb epimedium may be a promising radio-neuro-protective drug to prevent radiation-induced neuropsychological disorders.